Orlando Sentinel Chris Hays column - Hays, Chris (McClatchy - Tribune Business News, 2014)
Despite putting up ridiculous passing numbers, despite helping Florida receiver commitment Ryan Sousa and 2015 USF receiver commitment Deondre Farrier grab the attention of FBS coaches, Israel still had no offers. Cincinnati quarterbacks coach Darin Hinshaw, who played QB at UCF in the late 1990s, came to Orlando to see Israel's Lake Nona teammate Chris Ferguson, a senior lineman.